Application of the grain flipping probability model to heat assisted magnetic recording - Eason, Kwaku (2013)
Heat assisted magnetic recording (HAMR) is often lauded as one of the key technologies poised to replace conventional granular magnetic recording (CGMR). Conventional recording is expected to eventually fail because as the information-bearing grains continue to shrink, they become thermally unstable and will spontaneously flip due to excitations from the ambient temperature. HAMR grains are smaller and have larger anisotropies making them thermally stable, but